Mathematical Modelling Competencies of Prospective School Teachers in Mathematics Education: An Analysis Based on the Approach to Problem-Solving Situations - Barquero-Ocampo, Adriana (2025)
[Objective] The objective of the research was to determine the mathematical modeling competencies shown by a group of prospective teachers in Mathematics Teaching, in their fourth year of studies at the Universidad Nacional. [Methodology] For this purpose, a qualitative research was conducted with 20 prospective mathematics teachers during the first half of 2022, when they were required to solve a series of problems as part of a training program in mathematical modeling. The work done by the participants on two specific problems is presented. [Results] The participating prospective teachers demonstrated competencies in solving mathematical modeling problems when the situation presented has the necessary data and its solution requires a specific procedure. In situations that involved conducting research to gather additional information or data, and making assumptions, among other things, which could imply different solutions, the participants had difficulties in solving the problems. [Conclusions] The participants demonstrated their ability to handle and make sense of relevant data for solving mathematical modeling problems. However, when they needed to conduct research to gather additional information or data, they were unable to identify which data should be included in the problem-solving process. Their ability to search for information, connect a mathematical model with another problem situation or a known model, or validate the solution obtained for a problem, was limited. The results obtained could indicate that it is necessary to emphasize these types of activities in the teacher training programs, for their use as a teaching strategy in their professional practice.